1990
DOI: 10.2527/1990.68123987x
|View full text |Cite
|
Sign up to set email alerts
|

Practical means for estimating pork carcass composition

Abstract: Three hundred sixty-one market-weight barrow and gilt carcasses were physically dissected into bone, skin, fat and muscle. A three-variable multiple linear regression equation containing the same independent variables (warm carcass weight, 10th rib loin muscle area and 10th rib fat depth) used (U.S.) to determine pork carcass lean weight was found to be the most practical means for predicting weight of muscle standardized to 10% fat. Multiple linear regression equations containing more than three independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
4
17
0
Order By: Relevance
“…Carcasses were split down the midline and chilled for 24 h. To expose the total CSA of the longissimus muscle, carcasses were cut through the vertebrae (perpendicular to the vertebrae) and between the 10th and 11th costae. A plastic grid was used to measure the area of the longissimus muscle to the nearest 0.32 cm 2 (39).…”
Section: Methodsmentioning
confidence: 99%
“…Carcasses were split down the midline and chilled for 24 h. To expose the total CSA of the longissimus muscle, carcasses were cut through the vertebrae (perpendicular to the vertebrae) and between the 10th and 11th costae. A plastic grid was used to measure the area of the longissimus muscle to the nearest 0.32 cm 2 (39).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have reported only small effects of including flax in swine diets on pork loin muscle palatability (Ahn, Lutz, & Sim, 1996;Kouba, Enser, Whittington, Nute, & Wood, 2003;Matthews, Homer, Thies, & Calder, 2000), but detrimental effects could increase in products with higher levels of fat such as pork grinds or further processed products. In addition, these effects may be more pronounced in barrows, which are typically fatter than gilts (Allen, & Bray 1964;Orcutt, Forrest, Judge, Schinckel, & Kuei, 1990).…”
Section: Introductionmentioning
confidence: 94%
“…Numerous studies have been directed at developing an accurate, noninvasive method of estimating body composition that might be eventually used to develop a "value-based" marketing system (Forrest et al, 1986;Orcutt et al, 1990;Cross and Whittaker, 1992). Techniques that have been investigated include electromagnetic scanning (Kuei et al, 19891, optical probe (Garrett et al, 19921, electrical meat measuring equipment (Joyal et al, 19871, and bioelectrical impedance (Swantek et al, 1992).…”
Section: Introductionmentioning
confidence: 99%